Latihan Senam Aerobik Terhadap Tingkat Kesegaran Jasmani Siswa SMKN 1 Palangka Raya - Uket; Yeni (Jurnal Keolahragaan JUARA, 2021)
The level of physical fitness of students is a demand among students. The purpose of this study was to determine the effect of aerobic exercise on the physical fitness of SMK Negeri 1 Palangka Raya students. The research method used is the experimental method, namely examining differences in physical fitness levels using aerobic exercise as an experimental group and without using aerobic exercise as a control group. The sample size was 30 people, 15 people in the control group and 15 in the experimental group, students of SMK Negeri 1 Palangka Raya. The research instrument consisted of running 60 meters, hanging elbows, lying sitting, jumping upright, and running 1200 meters. The results of data analysis obtained t count of 9.75 while t table with a significant level of 5% (0.05) is 2.13, then t count is greater than t table 9.75 > 2.13 which means Ho is rejected and Ha be accepted. It is concluded that aerobic exercise affects the level of physical fitness in class XI students of SMK Negeri 1 Palangka Raya.